2020
DOI: 10.1002/app.49139
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐dried graphene oxide modified with trimethylhexamethylene in the mix solvent for improved anti‐corrosion property of epoxy

Abstract: Graphene oxide (GO) reinforcement to enhance the property of epoxy has been reported many times; with most of the papers focusing on how to modify GO with different functional groups to achieve better dispersion. Here, the importance of the preparation route on the coating systems performance was investigated. It was found that a mixed polar/nonpolar solvent BuOH/xylene (3/1 vol/vol) was the best choice for forming the epoxy/GO coatings. Furthermore, it was found that when the freeze‐dried GO sonicated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The variation in transmittance of peaks related to N–H bend (1611 cm –1 ), C–O stretch (1033 cm –1 ), and epoxide vibrations (916, 822 cm –1 ) was plotted in a bar diagram, normalized by the C–C stretch peak. These three peaks are highlighted because these represent the reaction of epoxy with the amine hardener during curing, as shown in Figure . …”
Section: Results and Discussionmentioning
confidence: 99%
“…The variation in transmittance of peaks related to N–H bend (1611 cm –1 ), C–O stretch (1033 cm –1 ), and epoxide vibrations (916, 822 cm –1 ) was plotted in a bar diagram, normalized by the C–C stretch peak. These three peaks are highlighted because these represent the reaction of epoxy with the amine hardener during curing, as shown in Figure . …”
Section: Results and Discussionmentioning
confidence: 99%
“…A higher density of blisters and the formation of micropores were found on the single nanofillers coating samples when the exposure time was increased to 500 h, signifying the amelioration of water, oxygen and corrosion ions at the coating–substrate interface, leading to the initiation of severe delamination of the coating. Hou et al 63 suggested that the presence of micropores in coating being detrimental as they represent a route for the salt solution to enter the coating. On the contrary, in the case of hybrid coatings, no apparent blisters were observed even after 500 h of exposure.…”
Section: Resultsmentioning
confidence: 99%